1989
DOI: 10.1083/jcb.109.4.1827
|View full text |Cite
|
Sign up to set email alerts
|

Precursors of chondroitin sulfate proteoglycan are segregated within a subcompartment of the chondrocyte endoplasmic reticulum.

Abstract: Abstract. Immunocytochemical methods were used at the levels of light and electron microscopy to examine the intracellular compartments of chondrocytes involved in extracellular matrix biosynthesis. The results of our studies provide morphological evidence for the compartmentalization of secretory proteins in the ER. Precursors of the large chondroitin sulfate proteoglycan (CSPG), the major proteoglycan species produced by chondrocytes, were present in the Goigi complex. In addition, CSPG precursors were local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 79 publications
4
30
1
Order By: Relevance
“…Our results show that such subcompartmentalization of the ER can also be observed in cells not exposed to BFA. On the other hand, morphologically different ER-derived structures have been shown to accumulate high amounts of HMG-CoA reductase in CHO cells (Chin et al, 1982) and to concentrate chondroitin sulfate proteoglycan precursors in chondrocytes (Vertel et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that such subcompartmentalization of the ER can also be observed in cells not exposed to BFA. On the other hand, morphologically different ER-derived structures have been shown to accumulate high amounts of HMG-CoA reductase in CHO cells (Chin et al, 1982) and to concentrate chondroitin sulfate proteoglycan precursors in chondrocytes (Vertel et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that proteins destined for incorporation into the ECM are segregated from one another at this early stage in secretion. In fact, in cartilage cells (chondrocytes), the distribution of aggrecan, a large secreted ECM proteoglycan that undergoes post-translational xylosylation in the early secretory pathway, has a distribution distinct from that of type II procollagen in the ER (Vertel et al, 1989). Such segregation could prevent premature interactions between matrix molecules and/or ensure proteinspecific post-translational modifications.…”
Section: Er-to-golgi Transportmentioning
confidence: 99%
“…However, other studies have suggested that the intermediate compartments are smooth tubular networks in continuity with the rough ER. Indeed, the budding compartment of mouse hepatitis virus (Krijnse-Locker et al, 1994), the site of accumulation of the E1 glycoprotein of the rubbella virus (Hobman et al, 1992), the site of concentration and assembly of chondroitin sulfate proteogycan precursors (Vertel et al, 1989), and the site of accumulation of vesicular stomatitis virus glycoproteins in cells injected with anti-␤-COP (Pepperkok et al, 1993) all showed smooth tubular networks in continuity with rough ER cisternae. These have been classified as intermediate compartments or as hypertrophied transitional ER lying along the main route of exocytic traffic.…”
Section: P97-dependent Ter Assemblymentioning
confidence: 99%